KOMUNIKASI ANTAR BUDAYA (Studi Tentang Komunikasi Antar Budaya di Kalangan Mahasiswa Suku Bugis dan Suku Konjo di Universitas Islam Ahmad Dahlan Sinjai - Muhlis, Muhlis; Suriyati, Suriyati; Musliadi, Musliadi; Firdaus, R Wahyudi; Syahria, Syahria (RETORIKA : Jurnal Kajian Komunikasi dan Penyiaran Islam, 2024)
This research aims to find out how intercultural communication works (study of intercultural communication among Bugis and Konjo ethnic students at Ahmad Dahlan Sinjai Islamic University. This research is field research, which is based on the results obtained through field research. The data collection technique is observation, interviews and documentation using data analysis, namely data reduction, data display and data verification. The main instruments in this research are the researchers themselves and other types of instruments that the researchers use as research instruments as follows: observation guidelines, interview guidelines, and communication tools The results of the research can be concluded that: First, the forms of communication that are often carried out by Konjo ethnic students and Bugis ethnic students at UIAD Sinjai are interpersonal communication, group communication and social media communication. Second, the communication barrier between Konjo ethnic students and Bugis ethnic groups is the use of the language of each tribe, the use of each dialect which sometimes causes misunderstandings